1976
DOI: 10.1111/j.1469-8137.1976.tb04658.x
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular‐arbuscular Mycorrhiza in Natural Vegetation Systems

Abstract: SUMMARYThe effects of vesicular-arbuscular (VA) mycorrhizal association on the growth of Festuca ovina L. were assessed in soils sterilized by irradiation, in unsterilized soil, and in sand or sandpeat cultures with various nutrient additions.In irradiated soils, effects of mycorrhizal infection were masked by nutrient release which proceeded through the first 4 months of growth. However, 9 months after inoculation, significant increases of yield and phosphorus content occurred in the mycorrhizal plants. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Despite studies of other species which demonstrate an increase in root: shoot ratio (e.g., Drew and Saker, 1975;Haynes and Goh, 1978;Chapin, 1980) and increasing mycorrhizal infection intensity (Hardie and Leyton, 1981;Ames et al, 1983) with decreasing soil fertility, no indication of increased allocation of either biomass or nutrients to roots or rhizomes were observed in these two perennial herbs when growing in relatively nutrient-poor sites. As growth rates ofthese longlived plants are difficult to measure under field conditions, we cannot determine whether increased mycorrhizal infection and tissue nutrient enrichment levels resulted in the degree of growth enhancement observed in greenhouse and garden experiments (e.g., Koucheki and Read, 1976;Bloss, 1982;Pope et al, 1983). Greenhouse growth studies are currently underway.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite studies of other species which demonstrate an increase in root: shoot ratio (e.g., Drew and Saker, 1975;Haynes and Goh, 1978;Chapin, 1980) and increasing mycorrhizal infection intensity (Hardie and Leyton, 1981;Ames et al, 1983) with decreasing soil fertility, no indication of increased allocation of either biomass or nutrients to roots or rhizomes were observed in these two perennial herbs when growing in relatively nutrient-poor sites. As growth rates ofthese longlived plants are difficult to measure under field conditions, we cannot determine whether increased mycorrhizal infection and tissue nutrient enrichment levels resulted in the degree of growth enhancement observed in greenhouse and garden experiments (e.g., Koucheki and Read, 1976;Bloss, 1982;Pope et al, 1983). Greenhouse growth studies are currently underway.…”
Section: Methodsmentioning
confidence: 99%
“…STUDIES OF vesicular-arbuscular mycorrhizal (VAM) relationships with perennial plants in natural ecosystems have repeatedly demonstrated that mycorrhizal plants take up more phosphorus and, in some cases, nutrients other than nonmycorrhizal plants (Stribley, Tinker and Rayner, 1980;Ames et al, 1983), exhibit greater drought tolerance (Hardie and Leyton, 1981;Allen, 1982) and grow at a faster rate (Koucheki and Read, 1976;Bloss, 1982;Pope et al, 1983). Such studies generally compare mycorrhizal and nonmycorrhizal plants, even though many wild plants are facultatively mycorrhizal (Janos, 1980) and may exhibit a range of mycorrhizal infection intensity depending on soil and site conditions (e.g., Allen, 1983;Anderson, Liberta and Dickman, 1984).…”
mentioning
confidence: 99%
“…There is now considerable evidence from laboratory experiments that a number of plant species benefit from vesicular-arbuscular (VA) mycorrhizal associations in terms of their growth rate (Koucheki & Read, 1976), drought tolerance (Fitter, 1988) or seedling survival (Janos, 1980). These apparent benefits are generally thought to result from improved phosphate uptake (Sainz & Arines, 1988;Wilson, 1988), since it is known that there is hyphal transport of P from beyond the root depletion zone (Sanders & Tinker, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…In the period between 112 and 40 das, all species show a decrease in growth rate. This can be mainly related to the higher proportion of cells that do not divide in relation to those that do [56], whereas, in annual crops, the highest growth occurs around 30 days after biofertilisation with an increase in the mean relative growth rate [57] and leaf area [58].…”
Section: Influence Of Endomycorrhizal Fungi On Plant Growthmentioning
confidence: 99%